Johannes Schmiedt, Proto-Physicus Gedanensis. Aetat. LXVI obiit A. MDCXC. / E. Hainzelmann. - Hainzelmann, Elias (1640-1693) (1690)
Przedstawia portret w popiersiu lekarza gdańskiego Johannesa Schmiedta (1623-1690).